The Anti-Inflammatory Potential of Fermented Red Ginger Extract (Zingiber officinale var. Rubrum) Against In Vitro Protein Denaturation - Kusdiharti, Meutia Sri; Dewi, Ni Wayan Rika Kumara; Artika, Made Prita (Jurnal Skala Husada : The Journal of Health, 2025)
Background:Red ginger (Zingiber officinale var. Rubrum) is known for many phytochemical components and various pharmacological activities, such as anti-inflammation. However, red ginger also has a high cellulose level. Special treatment is needed to degrade the cellulose so that phytochemicals can be maximally extracted. Trichoderma harzianum, a cellulase enzyme-producing fungus, can degrade cellulose and increase the efficiency of phytochemical extraction. Aims:This study aimed to evaluate the in vitro anti-inflammatory potential of red ginger extract fermented with T. harzianum. Methods:This research is an experimental method involving the fermentation of red ginger powder before extraction, followed by an in vitro protein denaturation inhibition assay using a UV-Vis spectrophotometer. Bovine Serum Albumin (BSA) was used as a negative control, diclofenac sodium as a positive control, and the fermented red ginger extract (FRGE) was tested at concentrations of 25, 50, 75, 100, and 125 ppm. The results: Phytochemical screening of FRGE confirmed the presence of alkaloids, flavonoids, saponins, phenols, and triterpenoids. The extract yield was 14.29%, with the highest inhibition of protein denaturation at 62.62% observed at 125 ppm. The IC50 value is 93.61 ppm. Conclusions: Based on these research results, FRGE had strong antiinflammatory potency in vitro. Keywords: Red ginger, Fermentation, Anti-inflammatory, Protein denaturation, Trichoderma harzianum